THE ROLE OF LIBRARIAN COMPETENCE IN IMPROVING EFFECTIVENESS IN MEMORABILIA SERVICES AT THE BUNG KARNO PROCLAMATION LIBRARY TECHNICAL IMPLEMENTATION UNIT - Dwi Rahmawati; Moch. Syahri; Rani Auliawati Rachman (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
This study aims to examine the role of librarian competencies in improving the effectiveness of memorabilia services at the Bung Karno Proclamation Library. As part of the preservation of national historical heritage, memorabilia services require technical, interpretive, and educational management. This study employs a descriptive qualitative approach, utilizing data collection techniques such as participatory observation, semi-structured interviews, and documentation. The findings reveal that librarian competencies, including internal motivation, personal traits, self-concept as custodians of cultural heritage, historical knowledge, and communication and technical skills, significantly contribute to service quality. Librarians not only act as collection managers but also as educational and cultural agents. Visitors' evaluations of librarians indicate high levels of satisfaction, particularly in terms of communication and information presentation. However, service effectiveness can still be improved through institutional support such as ongoing training, institutional policies, and the use of digital technology. These findings provide a clear practical basis for institutional policymakers to design continuous professional development programs and implement structural support policies to ensure the sustainability and cultural relevance of memorabilia services. This study recommends strengthening librarians' competencies holistically and fostering cross-institutional collaboration as strategies for enhancing sustainable and culturally relevant memorabilia services.